Effects of Ankle Foot Orthoses on Restricted Ankle Joint Dorsiflexion Due to Plantarflexors Stiffness in People with Stroke: A Scoping Review - Fahimeh Sadat Jafarian; Somaie Payehdar; Fateme Pol; Saeed Forghany (Shiraz University of Medical Sciences, 2019)
Background: Orthotic interventions such as different types of ankle foot orthoses have been widely suggested to either prevent or treat restricted ankle joint dorsiflexion and consequent equinus or equinovarus foot deformities in people with stroke. However, it is not clear whether orthotic interventions are effective against spasticity or stiffness. Therefore, this systematic review aimed to systematically review the effect of orthotic interventions on restricted ankle joint dorsiflexion due to plantarflexor stiffness. Review of literature: An electronic database search was performed using PubMed, ISI web of sciences, Scopous within 1990-2018. A set of search terms were derived from medical subject heading (MESH). A total of 486 potential articles were identified through database search. Following title screening and reviewing abstract, 60 articles were potentially relevant to undergo full consideration. Full text article review counted this number down to 2. Discussion: Studies found significant decreased plantarflexor stiffness indicated by increased ankle passive dorsiflexion range of motion after orthotic interventions. Conclusion: There are only a few studies which have objectively assessed the effects of orthotic interventions on restricted ankle joint dorsiflexion due to plantarflexor stiffness in stroke. A comprehensive study would provide insight into the effectiveness of orthotic interventions on restricted ankle joint dorsiflexion due to plantarflexor stiffness.